2006
DOI: 10.2116/analsci.22.1051
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Precipitation of Dyes from Dilute Aqueous Solutions of Ionic Liquids

Abstract: Due to their unusual properties, ionic liquids are garnering increased attention from academic and industrial research communities alike. 1 Almost every named synthesis and many more organic/inorganic/organometallic reactions have been reported in ionic liquids. 2 Novel analytical applications of ionic liquids are emerging every day; effective, and in some cases unique, utilizations of ionic liquids have been demonstrated in a variety of techniques encompassing electroanalysis, separation, extraction, spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…E T N in [bmim][PF 6 ] + PEG (average MW 200, 400, 600, and 1500) solutions thus obtained are listed in Table . The E T N in neat [bmim][PF 6 ] (0.67 ± 0.00 5 ) is similar to that observed in 3-methylphenol (0.67 ± 0.00 5 ) and close to that observed in tetraethylene glycol, 4-bromophenol, and 4-cyanophenol (0.66 ± 0.00 5 ). Our [bmim][PF 6 ] E T N is in agreement with what is reported by many researchers earlier. ,, , It is observed that E T N in neat [bmim][PF 6 ] is higher than those in neat PEGs indicating higher dipolarity/polarizability and/or HBD acidity of [bmim][PF 6 ] relative to that of PEGs. As expected, E T N decreases with increasing PEG average MW.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…E T N in [bmim][PF 6 ] + PEG (average MW 200, 400, 600, and 1500) solutions thus obtained are listed in Table . The E T N in neat [bmim][PF 6 ] (0.67 ± 0.00 5 ) is similar to that observed in 3-methylphenol (0.67 ± 0.00 5 ) and close to that observed in tetraethylene glycol, 4-bromophenol, and 4-cyanophenol (0.66 ± 0.00 5 ). Our [bmim][PF 6 ] E T N is in agreement with what is reported by many researchers earlier. ,, , It is observed that E T N in neat [bmim][PF 6 ] is higher than those in neat PEGs indicating higher dipolarity/polarizability and/or HBD acidity of [bmim][PF 6 ] relative to that of PEGs. As expected, E T N decreases with increasing PEG average MW.…”
Section: Resultssupporting
confidence: 90%
“…In this context, we have earlier reported our investigations on the effects of added water, ethanol, aqueous−ethanol, and other ionic liquids on different ILs. The miscibility of water and ethanol in the “hydrophobic” IL 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim][PF 6 ]) is significantly low (∼2.1 and ∼9.7 wt %, respectively, at ambient conditions), which, in turn, makes it difficult to modify the physicochemical properties of this common IL to any desired extent. Investigations on the addition of water and ethanol to PEGs also imply the changes in the physicochemical properties of these systems to be fairly limited …”
Section: Introductionmentioning
confidence: 99%
“…A series of physicochemical techniques, such as adsorption, 4 photocatalytic degradation, 5 electro-kinetic coagulation, 6 precipitation, 7 membrane ltration, 8 and occulation, 9 have been developed for the removal of dyes from waste water. Of these methods, adsorption emerges as a superior industrial water treatment method due to the simplicity of design, low cost, stability and reusability of the adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques have been applied for the removal of methyl orange such as precipitation [ 5 ], coagulation and flocculation [ 6 ], photodegradation [ 7 ], biological degradation [ 8 ], catalytic degradation [ 9 , 10 , 11 ], and adsorption [ 10 , 12 , 13 , 14 ]. Adsorption is considered among the best techniques for water treatment [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%